AC-CBS-Based Partitioned Semi-Implicit Coupling Algorithm for Fluid-Structure Interaction Using Stabilized Second-Order Pressure Scheme (Communications in Computational Physics, 2018)
We analyze in this paper the pressure splitting scheme of a partitioned semi-implicitcoupling algorithm for fluid-structure interaction (FSI) simulation. The semi-implicitcoupling algorithm is developed on the ground of the artificial compressibilitycharacteristic-based split (AC-CBS) scheme that serves not only for the fluid subsystembut also for the global FSI system. As the dual-time stepping procedure recommendedfor quasi-incompressible flows is incorporated into the implicit coupling stage, thefluctuating pressure may be unusually susceptible to the AC coefficient. Moreover, itis not trivial to devise an optimal AC formulation for pressure estimation. Instead,we consider a stabilized second-order pressure splitting scheme in the AC-CBS-basedpartitioned semi-implicit coupling algorithm. Computer simulation of a benchmarkFSI experiment demonstrates that good agreement is exposed between the availableand present data.